Evaluation of CO2 storage of water alternating gas flooding using experimental and numerical simulation methods. (1st March 2022) - Li, Zongfa; Su, Yuliang; Li, Lei; Hao, Yongmao; Wang, Wendong; Meng, Yang; Zhao, An
Highlights: Comparison of CO2 storage characteristics between continuous CO2 flooding and WAG. Key factors influencing CO2 storage of WAG. Maximizing CO2 storage amount of WAG using surrogate optimization. Abstract: The potential of water alternating gas (WAG) flooding in CO2 storage was exploited using experimental and numerical simulation methods in this study. Through comparing experiments results of WAG flooding and continuous CO2 flooding, WAG flooding after water flooding enhanced oil recovery by 39.0%, 2.2% higher than that of continuous CO2 flooding. However, the water slugs in WAG displaced part of the previously stored CO2 out the core. Only 13.1% of the injected CO2 was stored through WAG, 13.4% lower than that of continuous CO2 flooding. Then, numerical simulations of WAG and continuous CO2 flooding were conducted at a water flooded oil reservoir. The field-scale case study showed that the number of rounds of alteration from CO2 slug to water slug in WAG, the duration time of each round, and the CO2 injection time in each round were the main factors influencing CO2 storage. Improper design of influencing parameters led to 118, 986 tons lower CO2 storage through WAG than continuous CO2 flooding. Finally, to obtain the maximum CO2 storage, surrogate optimization was applied to adjust the proposed influencing factors. The optimization results showed less rounds of alteration and a pure CO2 slug size at the end improved the CO2 swept area in the reservoir for CO2 storage and inhibited the displacement of CO2 by water slug. After optimization of the proposed factors, 391, 000 tons of CO2 were stored in the water flooded oil reservoir through WAG flooding, 65, 764 tons more than continuous CO2 flooding. This study provides valuable experimental data and theoretical guidance for CO2 storage in water flooded oil reservoirs.